2003
DOI: 10.1136/thorax.58.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viruses in exacerbations of chronic obstructive pulmonary disease requiring hospitalisation: a case-control study

Abstract: Background: Acute exacerbations of chronic obstructive pulmonary disease (AE-COPD) are a common cause of hospital admission. Many exacerbations are believed to be due to upper and/or lower respiratory tract viral infections, but the incidence of these infections in patients with COPD is still undetermined. Methods: Respiratory syncytial virus (RSV), influenza A and B, parainfluenza 3, and picornaviruses were detected by nested reverse transcription polymerase chain reaction (RT-PCR) in upper (nasal lavage) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
402
4
42

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(465 citation statements)
references
References 30 publications
17
402
4
42
Order By: Relevance
“…Greenberg documented that 27% of exacerbations in 62 prospectively followed patients with COPD were related to a viral etiology (45); picornaviruses, parainfluenza virus, and coronaviruses accounted for the majority of infections in this study. Other investigators have suggested that up to 60% of exacerbations have been associated with viral infections, including picornaviruses, respiratory syncytial virus (RSV), influenza, and human metapneumoviruses (46)(47)(48)(49)(50)(51). One prospective study of hospitalized patients with AE-COPDs found a viral pathogen in more than 48% of episodes (vs. 6.25% in the stable state), with a similar distribution of viral pathogens as previously noted (52).…”
Section: Virusessupporting
confidence: 55%
“…Greenberg documented that 27% of exacerbations in 62 prospectively followed patients with COPD were related to a viral etiology (45); picornaviruses, parainfluenza virus, and coronaviruses accounted for the majority of infections in this study. Other investigators have suggested that up to 60% of exacerbations have been associated with viral infections, including picornaviruses, respiratory syncytial virus (RSV), influenza, and human metapneumoviruses (46)(47)(48)(49)(50)(51). One prospective study of hospitalized patients with AE-COPDs found a viral pathogen in more than 48% of episodes (vs. 6.25% in the stable state), with a similar distribution of viral pathogens as previously noted (52).…”
Section: Virusessupporting
confidence: 55%
“…Interestingly, chronic obstructive pulmonary disease (COPD) is associated with an exaggerated type 1 immune cell inflammatory infiltrate [7,27]. Chronic RSV infection has been reported in COPD [28] and acute COPD exacerbations are associated with RSV infection [29,30]. BORCHERS and co-workers [18,31] demonstrated that NKG2D ligand expression is induced on pulmonary epithelial cells in response to oxidative stress, and protein levels of cell-associated MICA were significantly increased in COPD patients who smoked.…”
Section: Ifn-c Increases Rsv-induced Il-15 Levels But Downregulates Rmentioning
confidence: 99%
“…Respiratory viruses, especially rhinoviruses, are an important cause of exacerbation and may be isolated in .50% of cases [6]. Rhinoviruses are also the viruses most frequently associated with the common cold [7].…”
mentioning
confidence: 99%